2010
DOI: 10.1016/j.ijid.2010.02.403
|View full text |Cite
|
Sign up to set email alerts
|

Sensivity and specifity of ELISA test for diagnosis of brucellosis

Abstract: e35214th International Congress on Infectious Diseases (ICID) Abstracts -Analysis of H. pylori virulence gene vacAs1 and cagA by conventional PCR method, emphasizing high sensitivity of PCR method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Diagnostic methods of brucellosis are usually based on detecting specific antibodies in the patient's serum. Nowadays many serological tests are applied for the diagnosis of human brucellosis (3,4), Most routine tests are serum agglutination tests based on Wright and 2-Mercaptoethanol (2-ME), which were developed in 1897 by Weight et al (5) and nowadays they are still used as reference tests in clinical laboratories. Other tests, which were developed later, include Rose Bengal, complement fixation, indirect coombs and the Enzyme Linked Immunosorbent Assay (ELISA) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic methods of brucellosis are usually based on detecting specific antibodies in the patient's serum. Nowadays many serological tests are applied for the diagnosis of human brucellosis (3,4), Most routine tests are serum agglutination tests based on Wright and 2-Mercaptoethanol (2-ME), which were developed in 1897 by Weight et al (5) and nowadays they are still used as reference tests in clinical laboratories. Other tests, which were developed later, include Rose Bengal, complement fixation, indirect coombs and the Enzyme Linked Immunosorbent Assay (ELISA) (6).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Mohraz et al, 9 the sensitivity and specificity of IgG ELISA were 93% and 100%, respectively. The sensitivity of IgG ELISA in the study by Peeridogaheh et al 10 was 75.4% which is less as compared to the studies done by Mohrazet al, 9 (93%) and Vakili et al ( 93.7%) 11 . However, the sensitivity of IgM ELISA in the study by Peeridogaheh et al 10 was higher that is 40.6% than that in Vakili et al, 11 (12.5%) study.…”
Section: Discussionmentioning
confidence: 67%
“…The sensitivity of IgG ELISA in the study by Peeridogaheh et al 10 was 75.4% which is less as compared to the studies done by Mohrazet al, 9 (93%) and Vakili et al ( 93.7%) 11 . However, the sensitivity of IgM ELISA in the study by Peeridogaheh et al 10 was higher that is 40.6% than that in Vakili et al, 11 (12.5%) study. The specificity of IgG ELISA of Mohrazet al, 9 study (100%) and IgM ELISA of Vakiliet al, 11 study (100%) support the result of Peeridogaheh et al 10 It is observed that from the review of literature, that it is difficult to compare seroprevalence of brucellosis in different studies as it varies from place to place and time to time.…”
Section: Discussionmentioning
confidence: 67%